Pengaruh Gaya Kepemimpinan Kepala Balai Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Pegawai Pada Balai Pelaksana Penyediaan Perumahan Ditjed Perumahan Kementerian PURR - Iswar, Diana Sari; Yustini, Tien (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Every agency has a policy in carrying out its duties and functions for all employees so that it can provide the best results for the agency. The leadership style possessed by a leader greatly influences the actions that will be taken to run and manage an organization. The right leadership style is a style that can improve performance, job satisfaction, and be adapted to various situations. High employee performance and satisfaction can help improve service quality which is an important key for government organizations that provide services to the public. The Housing Provision Implementation Center is a work unit under the Directorate General of Housing of the Ministry of Public Works and Public Housing to assist the President in organizing state government in the housing sector. There are 19 Housing Provision Implementation Centers in 34 provinces in Indonesia. The purpose of this study was to measure the effect of leadership style on employee performance on employee job satisfaction at the Housing Provision Implementation Center. The type of research used is quantitative, with a simple mediation analysis design. The research method uses primary data in the form of questionnaires with simple and multiple linear regression analysis. The sampling technique uses proportions taken from 19 Housing Provision Implementation Centers. The total sample was 95 employees. The results showed that the leadership style of the Head of the Hall was more participatory; the leadership style of the Head of the Hall affected employee performance; the leadership style of the Head of the Hall affected job satisfaction; the leadership style of the Head of the Hall affected performance through employee job satisfaction.